Studies on mechanical and dry sliding wear behaviour of graphite/flyash reinforced aluminium (Al6Mg) MMCs. (2020) - Rajesh, K.; Mahendra, K.V.; Mohan, N.; Sachit, T.S.; AkshayPrasad, M.
Abstract: The present research work aims to the development and study the self-lubricating behaviour of hybrid MMC's. Self-lubrication property of the composites exhibits better tribological properties as compared with other hybrid MMc's. In the present research work investigates the possibility of using graphite/flyash for synthesizing aluminium (Al6 Mg) based self-lubricating composite through stir casting technique. In this study keeping the flyash constant 8 wt% and by varying graphite (2–8 wt%). The distance, load, and velocity are the parameters are used for the study in the mechanical properties of composite were measured by using universal tensile testing equipment, Brinell hardness testing equipment and pin-on-disc test rig. The result reveals that the improvement in mechanical properties and tribological properties of filler filled composite specimen. Wear behaviour changes with respect to load and lowers the friction co-efficient with the effect of solid lubricants. The wear mechanism are studied by using scanning electron microscope (SEM).